2002
DOI: 10.1074/jbc.m202242200
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIIa Induces Tissue Factor-dependent Up-regulation of Interleukin-8 in a Human Keratinocyte Line

Abstract: Tissue factor (TF), a transmembrane receptor for the serine protease coagulation factor VII(a) (FVIIa), is the main initiator of the coagulation cascade. Through incompletely elucidated mechanisms, TF serves additional functions in tumor-associated angiogenesis and metastasis. We have studied interleukin-8 (IL-8) as a possible link between TF-FVIIa complex formation and subsequent processes. Recombinant human FVIIa induced the up-regulation of both IL-8 mRNA and protein in a FVIIa dose-and time-dependent fashi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…4). Consistent with other studies (19,20), we found that the transcriptional activity of the mutated promoters was significantly reduced compared with the wild-type construct whether transfected with Tid1 siRNA oligos or not (Fig. 4).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…4). Consistent with other studies (19,20), we found that the transcriptional activity of the mutated promoters was significantly reduced compared with the wild-type construct whether transfected with Tid1 siRNA oligos or not (Fig. 4).…”
Section: Resultssupporting
confidence: 81%
“…The higher level of cellular Tid1 S (but not Tid1HQ) markedly blocked cell migration induced by FVIIa, which coincides with the ability of Tid1 S (but not Tid1HQ) to block FVIIa-induced IL-8 production in MDA-MB231 cells. Because NF-nB is the dominant pathway for the induction of IL-8 by FVIIa (20) and because Tid1 negatively regulates NF-nB activity (Fig. 4), it is possible that Tid1 blocked FVIIa-induced IL-8 production by inhibiting NF-nB activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, colon epithelial cells are a known source of IL-8 in inflammatory conditions (46), and the FVIIa/TF complex was previously shown to induce IL-8 levels in several different cell lines (47)(48)(49). In agreement, we show that ex vivo FVIIa-dependent KC production is dramatically reduced in TFlow colon sections compared with colon sections of wild-type mice.…”
Section: S E P T E M B E R -O C T O B E R 2 0 1 1 T I S S U E F a Csupporting
confidence: 77%
“…Subsequent cellular events include the activation of p21Ras (Versteeg et al, 2003) and p42/p44 mitogen-activated protein kinase (MAP kinase) pathways (Poulsen et al, 1998;Camerer et al, 1999Camerer et al, , 2000bPendurthi et al, 2000;Versteeg et al, 2000). Furthermore, FVIIa induces the activation of the protein kinase B (PKB) pathway in TFexpressing cells, in turn producing enhanced protein synthesis (Versteeg et al, 2000(Versteeg et al, , 2002 and is also essential for FVIIa-induced production of IL-8 and other factors (Wang et al, 2002). Strikingly, both the p42/p44 MAP kinase and the PKB pathways are also known for their capacity to inhibit programmed cell death or apoptosis (Kennedy et al, 1997;Kulik et al, 1997;Bergmann et al, 1998;Kurada and White, 1998), but a possible link between TF and diminished apoptosis has not been investigated.…”
Section: Introductionmentioning
confidence: 99%